In the Hands of a Populist Authoritarian: The Agony of the Hungarian Asylum System and the Possible Ways of Recovery - Kriszta Kovács; Boldizsár Nagy (Migrants' Rights, Populism and Legal Resilience in Europe, 2022)
This chapter locates Orbanian discourse and measures on migration in a Schmittian paradigm. The theory of Carl Schmitt helps us make sense of Hungarian constitutional developments, because Orbán has continuously concentrated on the political friend and foe to maintain a permanent `crisis' situation. The chapter shows how Orbán's authoritarian goals have determined the management of regular migration and the control of irregular migration and especially asylum. Most rules applicable during the fictitious `state of crisis caused by mass immigration' in Hungary contradict EU law and breach international asylum law. The chapter argues that the `external constraining force' of the EU is nevertheless relevant both in the context of migration and for the possibilities of democratic resistance. The chapter finds potential for legal resilience on the international and EU level, whereas domestically techniques of democratic resistance developed during feudalism (e.g., the tradition of free cities or `passive resistance') and socialism (e.g., samizdat) can be mixed with those based on the leftovers of the rule of law regime.
Keywords: 320; Hungary; Victor Orbán; Carl Schmitt; migration; crisis; emergency; authoritarian populism; democratic resistance; legal resilience